Frailty in elderly community: socioeconomic and health characteristics – an observational study - Buranello, Mariana C.; Pegorari, Maycon S.; Castro, Shamyr S. de; Patrizzi, Lislei J. (Medicina (Ribeirao Preto), 2015)
Study design: Cross-sectional, observational and analytical study. Objective: To investigate the association between frailty syndrome with socioeconomic and health conditions in elderly community residents. Material and Methods: A sample of 54 elderly ascribed to the Family Health Team of Uberaba/MG. Data collection consisted of the evaluation of cognitive status, record of socioeconomic, health perception, morbidities, number of medications and the frailty phenotype, categorized into non-frail (GN) (no items of the phenotype), pre-frail (GP) (two items of the phenotype) and frail (GF) (three or more items of the phenotype). Results: 11.1% of the group was classified as frail, 46.3% as pre-frail and 42.6% as non frail. There was no significant difference for the socioeconomic and health variables between groups. However, the frail group had lower education and income, greater number of morbidities and predominantly female. The use of drugs was statistically higher in the frail group compared to pre-frail and non frail with 100% of the frail group consuming 3 or more medications. Conclusions: Drug consumption was higher for the frail elderly, indicating the need for special attention to this characteristic, given the different consumption profile shown. Furthermore, the findings of the study emphasize the importance of social components in elderly health impact seen in frailty condition